Rinse But Don't Repeat: Single Application V.A.C. VERAFLO Salvages Infected Breast Prostheses. (29th October 2021) - Antognoli, Lauren E.; Singh, Devinder P.; Choudhry, Salman; Turcotte, Justin; Holton, Luther H.
Abstract : Introduction: Existing salvage protocols for infected breast prostheses using negative pressure wound therapy with instillation and dwell (NPWTi-d) require multiple returns to the operating room and prolonged length of stay. We present our expedited salvage protocol and discuss outcomes and associated costs savings. Methods: Using a retrospective review, we identified 25 consecutive patients (27 breasts) with peri-prosthetic breast infection. Nine patients (10 breasts) underwent removal of infected breast prostheses followed by autologous or staged implant-based reconstruction. Sixteen patients (17 breasts) underwent our single application salvage protocol. A cost analysis was performed comparing the two groups, and an economic model was used to project the cost savings associated with using single application NPWTi-d protocol. Results: Fifteen of the 16 patients (94%) who underwent single application NPWTi-d had successful implant salvage. Average duration of NPWTi-d was 2 days, 7 hours, and average length of stay was 4.43 days. Compared to control, patients who received the single application protocol required significantly fewer hospitalizations and office visits. A total savings of 58, 275 could have been achieved by using the single application NPWTi-d protocol in the patients who did not undergo NPWTi-d. Conclusions: Single application of NPWTi-d is a simple, safe, and cost-effective technique for salvage of breast prostheses, with 94% success rate, even in immunocompromised patients and severe infection. Compared to previous protocols, ours requires fewer trips to the operating room, shorter length of stay, and more permanent implants placed during salvage. Our protocol is also associated with fewer office visits and fewer returns to the operating room.